Case report: Three-dimensionally printed patient-specific acetabular cage for revision surgery of aseptic loosening in a dog with micro total hip replacement - Kang, AhRan; Lee, Haebeom; Roh, Yoonho; Kim, Daehyun; Jeong, Seong Mok; Jeong, Jaemin (Frontiers in Veterinary Science, 2022)
A 2-year-old castrated male Pomeranian dog was presented for regular follow-up after micro total hip replacement (mTHR) 16 months prior to presentation. Clinically, the dog did not show any noticeable lameness of the left hindlimb, except for external rotation during walking. However, radiographic findings, namely rotation and medialization of the acetabular cup with a periprosthetic lucent line and bone formation medial to the acetabulum, were interpreted as aseptic loosening of the acetabular component. Because the dog was incompatible with the conventional THR revision method owing to severe bone defects in the acetabulum, a patient-specific titanium acetabular cage prosthesis with biflanges and four cranial and one caudal screw hole was designed for revision surgery. A custom-made acetabular cage was prepared, and it had a 12-mm polyethylene cup fixed with polymethylmethacrylate bone cement and positioned in the acetabulum. After the custom-made acetabular cage was anchored to the pelvic bone with the five cortical screws, reduction of the prostheses was achieved smoothly. The dog showed almost normal limb function without external rotation of the left hindlimb 2 weeks postoperatively. Bone remodeling and stable implant position were noted on radiographic images 3 years after revision surgery, with no evidence of loosening. Based on the clinical outcomes, the use of a custom-made acetabular prosthesis can be an effective treatment option for revision arthroplasty in acetabula with severe bone loss and structural changes in small-breed dogs.